ANALISIS KERENTANAN PADA SUATU WEBSITE MENGGUNAKAN TOOLS XSPEAR, XSSCON, DAN PWNXSS - Zulvan Avito Anwari; I Gede Pasek Wedana; Jaya Deva; Kadek Dwika Darma Widyaputra; Gede Arna Jude Saskara; I Made Edy Listartha (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
One way to conduct vulnerability analysis on websites as a preventive control is by scanning. The method used is applied research, focusing on analyzing the results of evaluation to provide information as input or to make certain decisions depending on the urgency of the objectives. Technically, this study will be carried out using 3 main stages of the process, namely determining project boundaries, implementing scanning on the website and analyzing the results of scanning that has been carried out. Scanning is done using XSpear, PwnXSS, XSScon and Acunetix Acuart software as the target website in testing. The scanning process on the Acunetix Acuart website based on the Kali Linux OS went well and resulted in the discovery of weaknesses or vulnerabilities. XSpear found 24 data vulnerabilities, PwnXSS found 45 data vulnerabilities, while XSSCon found 44 data vulnerabilities.